Long-term outcomes of intrastromal femtosecond laser presbyopia correction: 3-year results - Thomas, Bettina C.; Fitting, Anna; Khoramnia, Ramin; Rabsilber, Tanja Marina; Auffarth, Gerd U.; Holzer, Mike P. (British journal of ophthalmology, 2016)
Background/aims To analyse visual outcomes and corneal changes 3 years after intrastromal femtosecond laser presbyopia treatment. - Methods In a prospective, unicentric clinical trial, 25 presbyopic patients received INTRACOR treatment (Technolas femtosecond laser) on their non-dominant eye. Examinations were performed preoperatively as well as 1, 24 and 36 months postoperatively and included refraction, near, intermediate and distance visual acuity tests, reading speed, corneal topography, stray light measurement, endothelial cell count and slit-lamp examination. - Results Comparison of preoperative versus 36 months postoperative values showed in median an improvement of uncorrected near visual acuity (UNVA) from 0.70 logMAR to 0.10 logMAR (p<0.001). Corrected distance visual acuity (CDVA) was reduced from −0.10 logMAR to 0.00 logMAR (p<0.001). The spherical equivalent preoperatively was 0.625 D and after an initial myopic shift after 1 month (0.125 D) and 24 months (0.25 D), the 36 months value (0.50 D) returned to resemble the preoperative value in statistical terms (p=0.123). A significant corneal steepening of 1.50 D in the treated area was measured. Pachymetry (thinnest point) revealed a statistically significant, but clinically insignificant corneal thickening from 535 to 549 µm (p=0.033). Endothelial cell count did not change. 92.86% of patients felt comfortable with the surgery result. - Conclusion INTRACOR treatment after 36 months improved UNVA to varying degrees. The effect can be explained by a corneal steepening. An initial myopic shift was reversible. Reductions especially in CDVA have to be taken into account and therefore careful patient selection and information is obligatory. - Trial registration number NCT01164358 and NCT01025050, Results